Food Loss and Food Waste: A Literature Review in 2009-2018 - Mustamin; Rombe, Elimawaty; Hadi, Suryadi; Vesakha, Gatha (International Journal of Psychosocial Rehabilitation, 2020)
In almost the last decade, food waste and food losses have become interesting topics among researchers. This review of literacy is carried out in order to determine the extent to which research on food loss and food waste is carried out and the use of what methods are most often used. In this study, the main sources of research data are sixty scientific articles from the last few years, starting from 2009 to 2018, relating to food waste and waste. Search for scientific articles is done by using online search (via ProQuest, Elsevier, and Google Scholar) and using the keywords ’food loss and food waste.’. The results of the review found that research on food loss and food waste experienced an upward trend from 2011 to 2014. The comparison of the highest number of articles discussing food loss and food waste was in 2014 with seventeen scientific articles, and 2011 was the year that had the fewest articles, namely only one article. The results of the review also show that the most frequently used method is quantitative methods. There are thirty-four articles using quantitative methods and twenty-six articles using qualitative methods. It is strongly recommended further research be conducted to use qualitative methods regarding food loss and food waste.